Design and enhancement of radiofrequency cannula (RC) for chronic pain management - Kamaruddin, Shafie; Wan Yusoff., Wan Ahmad Yusmawiza; Mohamed, Rozilah @ Abdul Hadi (Trans Tech Publications Ltd, 2014)
The purpose of this paper is to give an overview of radiofrequency procedure, the main components of the procedure, critical issue concern with existing cannula design and proposed methodology in design and enhancement. The literature on radiofrequency procedure has been reviewed. The main issue or problem in existing design related to placement of cannula to target nerves which are ability to firmly hold the cannula and adjustment of the cannula to the target nerve. This study proposes the fabrication prototype cannula hub using Fused Deposition Modeling (FDM) machine. Essentially, this study may benefit a lot in providing alternative design of the cannula hub while promising a better performance of RF cannula.